THE INFLUENCE OF TAX UNDERSTANDING, CORETAX IMPLEMENTATION, AND CORETAX INFRASTRUCTURE ON INDIVIDUAL TAXPAYER COMPLIANCE - Elba Seville; Choirul Anwar; Ayatulloh Michael Musyaffi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2026)
This study aims to examine the influence of tax understanding, Coretax implementation, and Coretax infrastructure on individual taxpayer compliance in the use of Coretax. The study is based on the importance of optimizing the digital tax administration system through the implementation of Coretax as an effort to improve taxpayer compliance. The successful implementation of the system depends on several factors, including taxpayers' understanding of taxation, the implementation of Coretax, and the quality of the supporting infrastructure. This research employed a quantitative method with a survey approach. Primary data were collected by distributing questionnaires to 257 individual taxpayers in Jakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that tax understanding has a positive and significant effect on individual taxpayer compliance. Coretax infrastructure also has a positive and significant effect on individual taxpayer compliance. In contrast, Coretax implementation does not have a significant effect on individual taxpayer compliance. Therefore, the Directorate General of Taxes is expected to strengthen the implementation of Coretax by expanding outreach programs, providing continuous taxpayer education and technical assistance, and encouraging wider adoption of the system. These efforts, together with improvements in Coretax infrastructure, are expected to support higher levels of individual taxpayer compliance in the future.